2019
DOI: 10.1021/acsinfecdis.9b00211
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Physicochemical Properties of Phenylthiazole Compounds with Antibacterial Potency by Modifying the Lipophilic Side Chain

Abstract: Bacterial resistance to antibiotics is presently one of the most pressing healthcare challenges and necessitates the discovery of new antibacterials with unique chemical scaffolds. However, the determination of the optimal balance between structural requirements for pharmacological action and pharmacokinetic properties of novel antibacterial compounds is a significant challenge in drug development. The incorporation of lipophilic moieties within a compound’s core structure can enhance biological activity but h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…To prevent the formation of the suspected coordination polymer, we added an additional bidentate ligand (2,2′-bipyridine) to the synthesis and obtained the new dimeric complex, [Ga 2 L 3 (bpy) 2 ] (hereafter abbreviated as 1 ). The use of this aromatic co-ligand also significantly increased the lipophilicity of the complex, which has been previously correlated with antimicrobial potency. …”
Section: Resultsmentioning
confidence: 78%
“…To prevent the formation of the suspected coordination polymer, we added an additional bidentate ligand (2,2′-bipyridine) to the synthesis and obtained the new dimeric complex, [Ga 2 L 3 (bpy) 2 ] (hereafter abbreviated as 1 ). The use of this aromatic co-ligand also significantly increased the lipophilicity of the complex, which has been previously correlated with antimicrobial potency. …”
Section: Resultsmentioning
confidence: 78%
“…It was notable that OBMB- 6f exhibited a lower hemolytic rate (>512 μg/mL) than decyl derivative 6g (413.2 μg/mL). Moreover, it was reported that excessive lipid solubility was detrimental to the preparation of compounds into suitable dosage forms . Therefore, OBMB- 6f with a moderate C log P value (4.21) was selected as a representative compound for subsequent studies including cytotoxicity, bactericidal performance, antibiofilm activity, and drug-resistance development, as well as antibacterial mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…1 H NMR (DMSO-d 6 ) δ: 8.38 (d, J = 4.8 Hz, 1H), 8.02 (d, J = 8.4 Hz, 2H), 7.78 (d, J = 8.4 Hz, 2H), 7.72 (d, = 7.2 Hz, 2H), 7.47 (t, J = 7.6 Hz, 2H), 7.39 (t, J = 6.8 Hz, 1H), 6.87 (d, J = 4.8 Hz, 1H), 3.80−3.68 (m, 3H), 3.41−3.37 (m, 2H), 3.18−3.14 (m, 1H), 2.73 (s, 3H), 2.18 (s, 6H), 1.81−1.75 (m, 1H). 13 (23). After we followed the general procedure, using (S)-(−)-3-(dimethylamino)pyrrolidine (42 μL, 0.4 mmol), compound 23 was obtained as a yellow solid (0.07 g, 64%) with mp = 136 °C.…”
Section: ■ Methodsmentioning
confidence: 99%
“…One of our successfully discovered new antibacterial scaffolds is arylthiazole which demonstrated confirmed activity against a large panel of multidrug-resistant (MDR) Gram-positive pathogens. These compounds outperformed vancomycin in terms of their rapid bactericidal mode of action. , The structure–activity relationships (SARs) of the arylthiazole antibacterial core were studied from three different perspectives. Briefly, the biphenyl side chain revealed notable improvement in the antibacterial effect, while the short half-life of the first discovered lead compound was remarkably enhanced by inserting the CN linker within pyrimidine structure (Figure ).…”
mentioning
confidence: 99%